The influence of rice husk and tobacco waste biochars on soil quality - Amir Hamzah; Ricky Indri Hapsari; Rossyda Priyadarshini (Brawijaya University, 2017)
Heavy metal pollution in agricultural land threatens soil and food quality. Soil pollution could be remediate using biochar, but the effectiveness of biochar on soil quality improvement is determined by types of feedstock and pyrolysis temperature. This study was aimed to explore the effect of different types of biochar on soil properties. Biochar from rice husk and tobacco waste was applied to soil contaminated with lead and mercury. This study was conducted at Sumber Brantas, Malang East Java, and used a completely randomized design with three replicates. Heavy metals content was measured using AAS. The results of measurements were analyzed using analysis of variance at 5% and 1% significance levels. The initial analysis of the soil properties at the research site showed that the soil nutrient status was low, i.e. N (0.2 %), K (0.50 cmol+/kg), and CEC (5.9 me/100g) respectively, but soil pH was neutral (6.8). The research site also has crossed the threshold of heavy metal content for Hg (0.5 ppm), Pb (25.22 ppm), Cd (1.96 ppm), and As (0.78 ppm). Biochar added had a positive influence on soil characteristics improvement. It could increase the content of organic C, i.e. 35.12% and 31.81% and CEC (cation exchange capacity), i.e.30.56 me/100g and 28.13 me/100 g for rice husk biochar and tobacco waste biochar, respectively. However, N, P, and K contents were low i.e. N ( 0.33 and 0.30 %); P2O5 (148.79 and 152 ppm); K (1.58 and 2.11 mg/100g) for rice husk biochar and tobacco waste biochar, respectively.